Effect of Various Foaming Agents on Ceramic Foam from Solid Waste - Chenglin Zhao; Chunmin Wang; Zichen Xia; Congcong Jiang; Yiran Dong; Zihao Lan (Crystals)
Due to the significant amount of solid waste generated annually in China, the rational use of these wastes has become increasingly important. The production of foam ceramics is considered an effective method for the large-scale utilization of such solid waste. In this study, granite sawing mud was selected as the raw material, with SiC and MnO2 serving as foaming agent to prepare foam ceramics. The foaming behavior of sintered samples using different foaming agent was investigated to determine the most suitable type and amount of foaming agent for obtaining foam ceramics with excellent pore structures. Additionally, the effects of the foaming agent on the pore structure and physical mechanical properties of the foam ceramics were studied in detail. The results showed that SiC and MnO2 both resulted in the pronounced expansion to different extent, and increasing the content of foaming agent enhances foam expansion. The best dosage of SiC was 1%, the optimum additive amount of MnO2 is 2–3%. For SiC, the oxidation reduction reaction occurred between SiC and O2 to generate CO2/CO. For MnO2, firstly, the reduction of MnO2 to Mn2O3 occurred, and then the Mn2O3 dissolved in the glass melt and, subsequently, Mn3+ was reduced to Mn2+, leading to gas formation and foaming. Under the same dosage of foaming agent and preparation conditions, the sample prepared with SiC as the blowing agent has higher compressive strength, lower water absorption, and a more uniform pore structure.